Stress factors among physiotherapy students at a university in Gauteng, South Africa - Zander I. Collins; Chané Siepker; Kelebogile J. Ralehlaka; Boitshoko C. Molefe; Tiisetso C. Phala; Simphiwe A. Vilankulu; Makwena M. Sibuyi; Thembelihle S. Ntuli (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Physiotherapy students are highly susceptible to experiencing burnout during training. Prolonged exposure to stressful environments predisposes students to psychological morbidities.